Minimization of Economic Rent in Spatial Price Equilibrium - Smith, Vernon L. (Review of Economic Studies, 1963)
Journal Article Minimization of Economic Rent in Spatial Price Equilibrium Get access Vernon L. Smith Vernon L. Smith Lafayette and Stanford Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 30, Issue 1, February 1963, Pages 24–31, https://doi.org/10.2307/2296027 Published: 01 February 1963